MerTK Cleavage on Resident Cardiac Macrophages Compromises Repair After Myocardial Ischemia Reperfusion Injury. Issue 8 (29th September 2017) - DeBerge, Matthew; Yeap, Xin Yi; Dehn, Shirley; Zhang, Shuang; Grigoryeva, Lubov; Misener, Sol; Procissi, Daniel; Zhou, Xin; Lee, Daniel C.; Muller, William A.; Luo, Xunrong; Rothlin, Carla; et al.
Abstract : Rationale: : Clinical benefits of reperfusion after myocardial infarction are offset by maladaptive innate immune cell function, and therapeutic interventions are lacking. Objective : We sought to test the significance of phagocytic clearance by resident and recruited phagocytes after myocardial ischemia reperfusion. Methods and Results: : In humans, we discovered that clinical reperfusion after myocardial infarction led to significant elevation of the soluble form of MerTK (myeloid-epithelial-reproductive tyrosine kinase; ie, soluble MER), a critical biomarker of compromised phagocytosis by innate macrophages. In reperfused mice, macrophage Mertk deficiency led to decreased cardiac wound debridement, increased infarct size, and depressed cardiac function, newly implicating MerTK in cardiac repair after myocardial ischemia reperfusion. More notably, Mertk(CR ) mice, which are resistant to cleavage, showed significantly reduced infarct sizes and improved systolic function. In contrast to other cardiac phagocyte subsets, resident cardiac MHCII LO CCR2 − (major histocompatibility complex II/C-C motif chemokine receptor type 2) macrophages expressed higher levels of MerTK and, when exposed to apoptotic cells, secreted proreparative cytokines, including transforming growth factor-β. Mertk deficiency compromised the accumulation of MHCII LO phagocytes, and this was rescued in Mertk(CR ) mice. Interestingly, blockade of CCR2-dependent monocyte infiltration into the heart reduced soluble MER levels post-ischemia reperfusion. Conclusions: : Our data implicate monocyte-induced MerTK cleavage on proreparative MHCII LO cardiac macrophages as a novel contributor and therapeutic target of reperfusion injury. Abstract : Supplemental Digital Content is available in the text.